INFORMATIVE - COMMUNICATION TECHNOLOGIES DURING THE STUDY OF DISCIPLINE «THERAPEUTIC DENTISTRY» AT THE CHAIR OF THERAPEUTIC DENTISTRY IN HIGHER STATE EDUCATIONAL ESTABLISHMENT OF UKRAINE «UKRAINIAN MEDICAL STOMATOLOGICAL ACADEMY» - N.М. Ilenko; N.V. Kotelevska; O.M. Boychenko (Український стоматологічний альманах)
Long terms of training, a large amount of information and high requirements for professional training of students - modern conditions of the educational process in medical universities. High demands of modern programs for training can’t satisfy, relying only on traditional pedagogical methods of teaching. It is necessary to constantly search for new approaches to the organization of training, which are accompanied by modern information technologies.